El Movimiento de la Cultura Libre: un entramado de redes en pos de otros modos de circular la producción cultural-artística - Racioppe, Bianca (2013)
In this article the ways that artists, who choose to license their work by Creative Commons or Copyleft, link and associate are analyzed. These artists are members of The Free Culture Movement that proposes the free distribution of symbolic goods without subscribing to the strict guidelines of Copyright. Even though ideas of the free circulation of creative works are recent, they are based in a pre-modern (or pre-capitalist) period in which they were socially shared without paying royalties; in the actual context -crossed by the logic of Internet and digital technologies- sharing becomes “more accessible” and debate on intellectual property is updated. In this perspective, groups of artists and collectives have decided that other artists may have access to their work or derivations of it.